PkM Pelatihan Penggunaan Kompor Oli Bekas Sebagai Energi Alternatif Guna Membangun Usaha Home Industry Keripik Ubi Madu pada Kelompok Tani Mulia Sejahtera di Desa Wisata Tawangmangu Jawa Tengah - Agus Choirul Arifin; Farid Majedi; Noorsakti Wahyudi; Sundaru Guntur Wibowo; Bias Nur Elmira; Rahayu Mekar Bisono (JURNAL ABDIMAS DOSMA (JAD), 2023)
The village of Nglurah, which is located in Karang Anyar, is a producer of ornamental plants/flowers which are traded in various areas around and outside Java. Most of the population in this city work as flower farmers. Apart from being farmers, it turns out that the residents need other forms of economic improvement. Therefore, a home industry for honey sweet potato chips was initiated to support the community's economy. To carry out the home industry, it is necessary to take economic steps to become an independent entrepreneur, which is an important field to be developed. This development is carried out to encourage the economic revival of the community in various business fields. By providing training solutions to the residents of the Nglurah hamlet in the form of life skills, in the form of training in the use of used oil stoves to support the home industry of honey sweet potato chips, which can be used as a provision for the skills of residents, especially the Mulia Sejahtera farmer group in the plantation sector to be applied in daily life. day. Implementation of Community Partnership Program (PKM) activities in Partners. Target solutions are provided using training methods with direct practice models by mixing used oil to be used on stoves.